Indian Women in Leadership (Current Perspectives on Asian Women in Leadership, 2018)
This book provides intriguing insights into the development of highly qualified women leaders in diverse Indian contexts and their role at national and organizational levels. While India has made enormous economic strides in the past few decades, gender inequality and underutilization of female talent remain deeply rooted and widely spread in many parts of Indian society. This book addresses an urgent need to stop treating Indian women as under-developed human capital and begin realizing their potential as leaders of quality work. This book will fill the gap of research on international leadership for students, academics, and multinational organizations. .